Satisfaction of Schoolchildren with a Didactic Tool for Oral Health Promotion: Odonto App Kids - Solís Mazón, María Eugenia (2024)
Objective: To compare satisfaction with the use of the didactic tool for oral health promotion, Odonto App Kids, among schoolchildren from private and public educational units in the city of Riobamba, Chimborazo province, Ecuador. Methods: A feld study with a quantitative approach and experimental design, specifcally a pre-experimental type, was conducted. The population consisted of 111 children from basic education institutions in the city of Riobamba. Data were collected through a survey to measure levels of satisfaction and usability. Non-parametric inferential tests, Wilcoxon W and Mann-Whitney U, were used to compare the variables according to the type of institution. Results: There was a predominance of schoolchildren who framed the usability of Odonto App Kids in the high category (44.2%), while satisfaction results showed a predominance of the medium level (52.3%). The comparison values were: Mann-Whitney U (1481), Wilcoxon W (3434), and Z (-0.227), with a p-value = 0.821. Conclusions: No statistically signifcant differences were established between those enrolled in private educational entities compared to those in public ones.